Perancangan Alat Pembersihan Isi Usus Ayam pada Pembuatan Keripik Usus di UKM Bu Ayu Jombang - Kusuma, Dimas Fajar; Satoto, Handy Febri (SURYA TEKNIKA, 2024)
The UKM Keripik Usus Bu Ayu is a chicken intestine chip production industry located in Sambirejo Village, Jombang. The production output of chicken intestine chips ranges from 50 to 100 kg per day. Due to the limited manpower for cleaning chicken intestines, the process takes a long time, affecting production efficiency. It takes 30 to 45 minutes to clean one kilogram of chicken intestines. Anthropometric calculations are conducted to determine the dimensions of tools that will be designed to work more ergonomically and reduce fatigue. Anthropometric data measurements at UKM Keripik Usus Ibu Ayu involve 10 workers. To fulfill the needs of anthropometric data analysis, direct measurements are carried out to obtain data that will serve as the basis for determining the dimensions of the ergonomic chicken intestine cutter tool. Body dimensions such as Standing Elbow Height (TSB) and Hand Reach (JT) are used in designing the ergonomic chicken intestine cleaning tool. Two-dimensional anthropometric measurement data is adjusted to the 50th and 5th percentiles as required for tool dimensions to facilitate employee operations. The process of cleaning chicken intestines with a single-phase electric motor dynamo system at Bu Ayu's chicken intestine chip SME enables rapid and efficient processing of chicken intestine contents. The new chicken intestine cleaning machine system equipped with rollers reduces fatigue and increases time efficiency by 70.17% compared to manual cleaning.